2015
DOI: 10.14499/indonesianjpharm26iss2pp71
|View full text |Cite
|
Sign up to set email alerts
|

PREPERATION AND CHARACTERIZATION OF Β-Cyclodextrin INCLUSION COMPLEXES ORAL TABLETS CONTAINING POORLY WATER SOLUBLE GLIMIPIRIDE USING FREEZE DRYING METHOD

Abstract: Glimepiride is an oral antidiabetic drugs which is practically insoluble in water. The formation of β-cyclodextrin inclusion complex was able to increase the solubility of glimepiride. This study aim to prepare, characterize and formulation of inclusion complex tablets in order to meet the requirement in Pharmacopeia. The inclusion complex were prepared in a molar ratio of 1:1 and 1:2 by freeze drying method, after that characterized include FTIR spectroscopy and scanning electro microscope (SEM). Further, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…4 Recent publications reported that cyclodextrins improved solubility and dissolution of itraconazole, curcumin, repaglanid, mirisetin, and glimepiride. [5][6][7][8][9] Spray drying method is one method that has been widely used to evaporate solvent for the formation of complex inclusion of poorly water-soluble drugs with β-cyclodextrin. The results of aripiprazole-β-cyclodextrin inclusion complex prepared by spray drying technique showed that this techniques could increase solubility and dissolution rate of aripiprazole.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent publications reported that cyclodextrins improved solubility and dissolution of itraconazole, curcumin, repaglanid, mirisetin, and glimepiride. [5][6][7][8][9] Spray drying method is one method that has been widely used to evaporate solvent for the formation of complex inclusion of poorly water-soluble drugs with β-cyclodextrin. The results of aripiprazole-β-cyclodextrin inclusion complex prepared by spray drying technique showed that this techniques could increase solubility and dissolution rate of aripiprazole.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, CDs and their derivatives show the ability to increase the solubility, stability, dissolution rate, and bioavailability of poorly soluble drugs through the formation of inclusion complexes and thereby are widely used for pharmaceutical applications. In addition, the advantages of CDs as a carrier also include (1) chemical derivatization by site-specific substitution; (2) the tunable cavity sizes; and (3) low toxicity and immunogenicity ( Kurkov and Loftsson, 2013 ; Syukri et al, 2015 ). The drug molecules can be partially or entirely inserted into the hydrophobic CD cavity under the driving forces of hydrophobic, electrostatic, van der Waals, charge-transfer interactions, etc.…”
Section: Delivery Vectors For Biomedical Therapymentioning
confidence: 99%
“…The images of the samples were taken at an excitation voltage of 10 kV. 39 Fourier Transform Infrared Spectroscopy. The analysis was performed on a Fourier transform infrared spectrophotometer (Bruker) to determine functional groups of glimepiride, Captisol, physical mixture, and inclusion complexes.…”
Section: S K Cementioning
confidence: 99%